Economic Valuation of Mangrove Forest Ecosystem in Teluk Ambon Baguala District - Revalda Amanda Yacoba Bribka Salakory; Nuddin Harahab; Bagyo Yanuwiadi (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
This study aims to describe about economic valuation of mangrove forest ecosystem in Teluk Ambon Baguala District. This research is a quantitative research. Data were collected through interviews, documentation and observation. Method analysis employed was total economic value. Overall, the economic value of mangrove forest ecosystem service is Rp. 7.273.222.250 per year, with the following description: Passo for Rp. 3.858.009.750 per year, Negeri Lama for Rp. 945.628.100 per year, Desa Nania for Rp. 650.750.400 per year and Waiheru for Rp. 1.818.834.000 per year.